Alveolitis, factors that predispose its appearance - Yudit Berrio Rey; María Elena Rey Ávila; Xiomara Suárez Morales (Acta Médica del Centro, 2014)
The extraction is the surgical procedure by erupted teeth are extracted from their alveoli with minimal trauma. The alveolitis is one of the most painful complications that can arise due to a disturbance in the alveolar wound healing resulting  a tooth extraction. It is considered that alveolitis is a multifactorial condition that the offending agents are numerous and can have a variable effect on the pathogenesis of the process. In the opinion of the authors is very important that the Specialist in Stomatology is able to pinpoint the factors that are associated with the origin of the alveolitis in its population to thereby plan and implement actions aimed at eliminating these causative agents, and therefore decrease the incidence of this condition so painful.